2008
DOI: 10.1590/s0103-50532008000800018
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptide synthesis in biphasic medium: evaluating the use of commercial porcine pancreatic lipase preparations and the involvement of contaminant proteases

Abstract: Sínteses bem sucedidas de dipeptídeos a partir de Ac-L-Tyr-OEt ou Z-L-X-OMe (X: Asp, Tyr, Phe, Arg, Lys ou Thr) e glicina amidada em meio reacional bifásico foram realizadas usando dois tipos de preparações comerciais de lipase pancreática suína (PPL) (bruta (cPPL) e purificada (pPPL)). Nas mesmas condições reacionais, a α-quimotripsina, protease pancreática que também apresenta atividade esterásica, catalisou a síntese de Ac-L-Tyr-Gly-NH 2 com alta produtividade. Na maioria das sínteses também ocorreu a hidró… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Bioreduction reactions were performed during 9 days at 28 ºC in potato dextrose broth using 6,8,10,12,14,15,20, 30 and 40 μL of acetophenone 1a to obtain (S)-1-phenylethanol in high to excellent enantiomeric excess (Table 5).…”
Section: Quantity Of Substratementioning
confidence: 99%
See 1 more Smart Citation
“…Bioreduction reactions were performed during 9 days at 28 ºC in potato dextrose broth using 6,8,10,12,14,15,20, 30 and 40 μL of acetophenone 1a to obtain (S)-1-phenylethanol in high to excellent enantiomeric excess (Table 5).…”
Section: Quantity Of Substratementioning
confidence: 99%
“…7 The use of microorganism new strains as biocatalysts may offer an alternative opportunity to investigate the local resources for the effective conduct of key synthetic transformations with significant economic and ecological implications. 8 Our research interest is based on the development of chemoenzymatic methodologies to obtain chiral alcohols using Brazilian local sources of low cost. Herein, we report our current investigations in the study of the Candida tropicalis CE017 strain behavior as a novel stereoselective reducing agent of aromatic prochiral ketones to the corresponding chiral alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Since acetylated Hmb (AcHmb) as the amide backbone protecting group led to a substantial improvement in the solubility of the synthetic bA4 amyloid fragment (34)(35)(36)(37)(38)(39)(40)(41)(42) [125], they concluded that the 2-hydroxy moiety was Hmbs essential feature and proposed the 2-hydroxybenzyl (Hbz) group, TFA-stable and trifluoromethanesulfonic acid (TFMSA) labile, for SPPS by the Boc/Bzl strategy. Since acetylated Hmb (AcHmb) as the amide backbone protecting group led to a substantial improvement in the solubility of the synthetic bA4 amyloid fragment (34)(35)(36)(37)(38)(39)(40)(41)(42) [125], they concluded that the 2-hydroxy moiety was Hmbs essential feature and proposed the 2-hydroxybenzyl (Hbz) group, TFA-stable and trifluoromethanesulfonic acid (TFMSA) labile, for SPPS by the Boc/Bzl strategy.…”
Section: Use Of Amide Backbone Protectionmentioning
confidence: 99%
“…[21][22][23][24] Nevertheless, since then, its main limitation has become apparent: it is mostly applicable to the production of peptides containing up to 5 amino-acid residues. 16,25,26 In addition, it is well known that the technology has disadvantages that make it impractical for reuse and recovery from reaction media, including use of puried proteases and expensive autolytic enzymes with short half-lives in solution. To overcome these limitations and reduce costs, many researchers have immobilized the proteases using a large variety of solid supports, [27][28][29][30] including nanoparticles.…”
Section: Introductionmentioning
confidence: 99%